POLA GEOMETRI PADA SENI DAN ARSITEKTUR ISLAM DI ANDALUSIA - Pramono, Andi (Journal of Islamic Architecture, 2011)
The most famous Islamic cultural heritages is the use of geometric patterns in Islamic art and architecture. This can be seen from the historical buildings that still exist in Alhambra which is located in Granada city, Andalucia, southern Spain. The way to make a layout plan, fasade, and ornaments that decorate the buildings were arranged in a simple mathematical art. The designing and building technique of Alhambra is based on geometry with the 1:5 ratio method. Â  Keywords: Â Islamic art, geometry, Alhambra